The Effectiveness of Language-Specific Personal Care Education on Improving the Knowledge and Skills of Vietnamese American In-Home Supportive Service Caregivers. (January 2023) - Vu, Thu Hoang; Ju, Eunae; Rousseau, Julie; Gibbs, Lisa; Saville, Neika; Lee, Jung-Ah
Background: In-Home Supportive-Services (IHSS) caregivers provide personal care assistance to low-income older adults. According to the California Social Service Department, 20.2% of IHSS caregivers spoke Vietnamese in one county. The purpose of this project was to improve the knowledge and skills among these Vietnamese American caregivers by providing a language-specific and culturally appropriate education on personal care. Methods: The project used a pre- and post-test design. Under the guidance of nursing faculty, four Vietnamese-speaking nursing students provided a 2-hr educational program on personal care (e.g., bathing, oral care) to registered Vietnamese IHSS caregivers. A pre- and post-survey was conducted. Results: Overall, 55 caregivers completed the surveys. The surveys showed significant increases in confidence in knowledge and skills related to personal care topics (all p s < .001). Conclusion: The findings demonstrated that the cultural and language-specific education was effective in increasing knowledge and confidence of Vietnamese IHSS caregivers related to personal care for older adults.